Elemental Sulfur-Mediated Transformation of Carboxylic Acids to Acyl Fluorides by Electrophilic Fluorinating Reagent, Selectfluor - Mahmoud, Elsayed M.; Mori, Soichiro; Sumii, Yuji; Shibata, Norio (Organic letters, 2023)
The elemental sulfur-mediated synthesis of acyl fluorides from carboxylic acids is achieved using Selectfluor. A broad range of acyl fluorides are accessible from carboxylic acids while avoiding the formation of acid anhydrides. 19F NMR spectra suggest that S8-fluoro-sulfonium cation A and neutral S8-difluoride A′ generated in situ are the reactive species in this deoxyfluorination reaction.